Phosphorescent tracer particles for Lagrangian flow measurement and particle tracking velocimetry - Kemp, L.; Jamieson, Elizabeth C.; Gaskin, S. J. (Experiments in fluids, 2010)
A new technique for manufacturing neutrally buoyant phosphorescent tracer particles for use in Lagrangian flow measurement and particle tracking velocimetry is presented. The particles can be manufactured with inexpensive equipment and materials, using three ingredients: paraffin wax, Keywax (a wax–rubber polymer) and LumiNova ® phosphorescent pigment. Particles can be made with a range of diameters (150–4,000 μm) and, when seeded throughout the flow, can be excited at the peak excitation wavelength of the pigment using a focused source of ultraviolet light. Under a range of lighting conditions, it is possible to excite a single particle or a chosen region of the flow to record and analyze their Lagrangian flow path. To demonstrate this technique, sample images are provided for flow in a laboratory channel with a side embayment.